A warming-yang herbal decoction protects against high-altitude hypoxia–induced osteoblast injury through modulation of HIF-1 signaling - Liu, Xuehai; Qi, Yaqian; Zhao, Rui; Jia, Binkui; Lei, Xilin; Li, Hongfan; Wang, Di; Zhang, Haoling; Wang, Wei; Song, Zhijing (Frontiers in Pharmacology, 2025)
ObjectiveThis paper systematically explored dental osteoblast injury at high altitude hypoxic condition and examined the protective role of warming-yang traditional medicine, Aconitum carm michaelii and Zingiber officinale decoction (GAWD) in this condition.MethodsWe constructed an in-situ high-altitude hypoxic model (4,500 m) with MC3T3-E1 osteoblastic cells and conducted RNA-seq analysis for Differentially Expressed Genes (DEGs). We performed enrichment analyses (GO, KEGG, and the Reactome pathway mapping) to reveal the relationships among the DEGs and key pathways. To further verify our results, we conducted a series of functional assays, including Cell Counting Kit-8 (CCK-8) for cell viability; flow cytometry assessment of reactive oxygen species (ROS); jc-10-based evaluation of mitochondrial membrane potential (MMP), and alkaline phosphatase (ALP) activity serum.ResultsTranscriptome profiling revealed that the hypoxia-inducible factor-1 (HIF-1) signaling pathway was central in the mediator role of osteoblast injury. High altitude hypoxia greatly suppressed the expression of HIF-1α, HIF-1β, von Hippel–Lindau tumor suppressor gene (VHL) and vascular endothelial growth factor (VEGF), resulting in increased intracellular ROS, calcium overload, mitochondrial distress, G1-phase cell cycle arrest, apoptosis, and decreased proliferation. Rehabilitation by GAWD recovered these impairment effects: cell viability and apoptotic protein expression were improved, ROS and intracellular Ca2+ were reduced, and mitochondrial membrane potential was regained, HIF-1/VEGF axis was recovered, apoptotic signaling and gross morphological injury were attenuated, and overall osteoblastic function was restored.ConclusionThe findings implicated HIF-1 signaling dysregulation in inducing high-altitude hypoxia–induced osteoblast injury and osteoporosis. GAWD may reduce hypoxia–induced cellular stress through recovering redox homeostasis and adjusting HIF-1/VEGF signaling. Collectively, this, study offers early molecular evidence supporting the utility of GAWD as a traditional Chinese medicine–based intervention for the prevention of bone metabolic disorders due to chronic hypoxic exposure.